2017
DOI: 10.1515/sspjce-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Cement Materials Based on Cellulosic Fibers for Plasters

Abstract: This paper presents physical and mechanical properties of cementitious composites/plasters containing cellulosic fibers in portion 2.0% and 5.0% of filler replacement after 28 days of hardening. Cellulosic fibers (Greencel) originated from bleached wood pulp and unbleached waste paper used in this experimental work were characterized from the point of view cellulose structure. Experimental investigations reveal that adding cellulosic fibers reduces composites density (up to 8.2 %) in comparison with composites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Technical conditions". Findings of experiment [6] showed that fibers of cellulose extracted from waste paper possess following properties: specific gravity -1,5 g/сm 3 , elastic modulus -133 GPа, deformation at break -3…6%. Computer diagnostics of morphometric parameters of cellulose fibers was performed with the use of ImageJ program: length (L f ), width (d f ), the area of projection (А f p ), the area of cross section (S f ), the common area of surface (А ф o ), volume (V f ), coefficient of cross section form (К f S ) were performed with the help of the program ImageJ [3].…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Technical conditions". Findings of experiment [6] showed that fibers of cellulose extracted from waste paper possess following properties: specific gravity -1,5 g/сm 3 , elastic modulus -133 GPа, deformation at break -3…6%. Computer diagnostics of morphometric parameters of cellulose fibers was performed with the use of ImageJ program: length (L f ), width (d f ), the area of projection (А f p ), the area of cross section (S f ), the common area of surface (А ф o ), volume (V f ), coefficient of cross section form (К f S ) were performed with the help of the program ImageJ [3].…”
Section: Methodsmentioning
confidence: 96%
“…Synthetic fibers contribute into formation of optimal mineral framework and reduce of shrinkage deformations of foam concrete. Authors assume that besides advantages mentioned above, the use of discreet fibers gives an opportunity to reduce the structural weight , improvement of heat-shielding characteristics and fire-resistance of wall fences [6,7]. The term "cellulose fiber" represents the group of fibers that derive from timber and plants, which differ in size, thickness, form and fiber durability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation